Negative electrode material and preparation method thereof, negative electrode sheet and battery
By introducing carbon layer, nanocellulose and phosphorus-molybdenum compounds into the silicon-based anion-based anion material, a dual anion-doped silicon anion-doped silicon anion material was prepared, which solved the problem of electrochemical performance decline caused by volume expansion and significantly improved the lithium-ion battery. Electrochemical properties.
Patent Information
- Application Number
- CN202310561212.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-05-18
AI Technical Summary
The lithium battery of existing silicon-based negative electrode materials has ruptured/generated solid electrolyte interface (SEI) film due to volume expansion, reducing electrochemical performance, and nanoification increases lithium consumption and reducing the ratio of first charge and discharge.
By calcining silicon powder in hydrocarbon gas to obtain carbon-encapsulated silicon powder and mixing it with nanocellulose and phosphorus-molybdenum compounds, a bianion-doped silicon negative electrode material was prepared, and the silicon anion-doped silicon negative electrode material was sprayed, dried, grinded, sintered, etc. The steps are obtained to obtain the negative electrode material.
This method improves the electrochemical performance of lithium-ion batteries, reduces the stress and strain caused by volume expansion, reduces the side reaction with the electrolyte, and improves the circulation performance of the negative electrode material.
Smart Images

Figure CN116598455B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to negative electrode materials and preparation methods thereof, negative electrode plates and batteries. Background Art
[0002] In recent years, silicon has been used as a potential negative electrode material for lithium ions (4200mAh / g, Li 22 Si5), has attracted much attention due to its high abundance and application theoretical capacity that is ten times higher than that of graphite anode (372mAh / g, LiC6), as well as its low discharge potential (about 0.4V).
[0003] The current silicon-based negative electrode materials mainly include pure Si phase negative electrode materials and SiO x (0<x<2) phase negative electrode materials. Compared with pure silicon, SiO x Although the volume change of lithium insertion is low, the theoretical specific capacity (2400mAh / g) is low, so the upper limit of the designed capacity is low. In addition, lithium insertion will form irreversible lithium silicate compounds Li4SiO4, which will reduce the initial charge and discharge rate of the battery and restrict the SiO x development. The volume expansion of pure silicon causes the solid electrolyte interface (SEI) film on the silicon surface to continuously rupture / form, resulting in a decrease in electrochemical performance. In order to solve these problems, various anode materials have been reported, such as nano-Si, porous Si, surface carbon core-shell composite materials, etc. to buffer the volume expansion of silicon during delithiation. However, nano-sizing increases the contact area between silicon and the electrolyte, resulting in an increase in electrolyte side reactions and an increase in lithium consumption, thereby reducing the battery's first charge and discharge ratio. Therefore, the electrochemical performance of lithium batteries using existing silicon-based negative electrode materials is still insufficient.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] The purpose of the present application is to provide a negative electrode material and a preparation method thereof, a negative electrode plate and a battery. The negative electrode material prepared by the preparation method is beneficial to improving the electrochemical performance of the battery.
[0006] This application is implemented as follows:
[0007] In a first aspect, the present invention provides a method for preparing a negative electrode material, comprising:
[0008] calcining silicon powder in a hydrocarbon gas to obtain carbon-coated silicon powder;
[0009] preparing a cellulose dispersion containing nano-cellulose and phosphorus-nitrogen salt;
[0010] The carbon-encapsulated silicon powder is mixed with a cellulose dispersion and dehydrated to obtain a silicon-cellulose mixture;
[0011] preparing a negative electrode material dispersion containing a silicon-cellulose mixture, a lithium source and a phosphorus-molybdenum compound;
[0012] The negative electrode material dispersion is sprayed, dried, ground and sintered in sequence to obtain the negative electrode material.
[0013] In an optional embodiment, the particle size of the silicon powder is 0.6-15 μm.
[0014] In an optional embodiment, the step of calcining silicon powder in a hydrocarbon gas to obtain carbon-encapsulated silicon powder comprises:
[0015] The silicon powder is sintered at 700-950°C for 1-5h in a mixed gas atmosphere of hydrocarbon gas and inert gas;
[0016] The temperature is then lowered to 400-700° C. and maintained for 1-5 hours to obtain carbon-encapsulated silicon powder.
[0017] In an optional embodiment, the hydrocarbon gas is a low-carbon chain gas with 1 to 8 carbon atoms, and the volume ratio of the hydrocarbon gas to the inert gas is (1 to 5):(5 to 20).
[0018] In an optional embodiment, the step of preparing a cellulose dispersion containing nano-cellulose and phosphorus-nitrogen salts comprises:
[0019] The nanocellulose is mixed with a dispersant solution, subjected to ultrasonic dispersion and stirring, and then a phosphorus-nitrogen salt is added to obtain a cellulose dispersion;
[0020] The dispersant solution includes at least one of dimethylformamide, sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium alkyl sulfonate.
[0021] In an optional embodiment, 0.01-0.4 kg of nano-cellulose is mixed with each liter of dispersant solution.
[0022] In an optional embodiment, the phosphorus-nitrogen salt is at least one of ammonium hydrogen phosphate, ammonium phosphate, magnesium ammonium phosphate, ammonium tripolyphosphate and ammonium polyphosphate; the nano-cellulose is at least one of cellulose nanowhiskers, nanofibril cellulose, nanofibrillated cellulose, microfibrillated cellulose and nano bacterial cellulose.
[0023] In an optional embodiment, the length of the nanocellulose is 50-500 nm and the diameter is 10-100 nm.
[0024] In an optional embodiment, the step of mixing carbon-encapsulated silicon powder with a cellulose dispersion and dehydrating to obtain a silicon-cellulose mixture comprises:
[0025] 400-800 g of carbon-encapsulated silicon powder is added to each liter of cellulose dispersion, and ultrasonic dispersion and stirring are performed. After heating and gas extraction, dehydration is performed at 100-110° C. to obtain a dry silicon-cellulose mixture.
[0026] In an optional embodiment, the step of preparing a negative electrode material dispersion containing a silicon-cellulose mixture, a lithium source and a phosphorus-molybdenum compound comprises:
[0027] Adding a lithium source and a phosphorus-molybdenum compound into an acid solution having a pH value of 3.5 to 6.5 to obtain a modified solution;
[0028] 1.5-5 kg of silicon-cellulose mixture is added per liter of modified solution to obtain a negative electrode material dispersion.
[0029] In an optional embodiment, the lithium source is at least one of lithium hydroxide, lithium oxalate, lithium chloride, lithium formate, lithium carbonate and phenyl lithium; and the acid solution is nitric acid solution, hydrochloric acid solution or phosphoric acid solution.
[0030] In an optional embodiment, the step of spraying, drying, grinding and sintering the negative electrode material dispersion in sequence to obtain the negative electrode material comprises:
[0031] Use a spraying machine to spray the negative electrode material dispersion at 45-95°C, and then dry and grind;
[0032] The product is sintered at 400-900° C. in a protective gas for 1-5 hours, and then ball-milled after cooling to obtain a negative electrode material.
[0033] In an optional embodiment, the phosphomolybdenum compound is at least one of ammonium phosphomolybdate, phosphomolybdic acid and molybdenum phosphide.
[0034] In a second aspect, the present application provides a negative electrode material, comprising silicon powder, a carbon layer coated on the surface of the silicon powder, carbonized nanocellulose attached to the surface of the carbon layer, and molybdenum phosphide, wherein the carbon layer and / or the carbonized nanocellulose are doped with nitrogen, phosphorus, and lithium elements.
[0035] In an optional embodiment, the lithium content in the negative electrode material is 0.002 to 5 wt%;
[0036] and / or, the molybdenum content in the negative electrode material is 0.001 to 0.2 wt%;
[0037] and / or, the nitrogen content in the negative electrode material is below 0.8 wt %, and the phosphorus content in the negative electrode material is below 0.8 wt %;
[0038] And / or, the particle size of the negative electrode material ranges from 0.2 to 15 μm.
[0039] In a third aspect, the present application provides a negative electrode plate, comprising a negative electrode material prepared by the method for preparing a negative electrode material according to any embodiment of the first aspect, or comprising a negative electrode material according to any embodiment of the second aspect.
[0040] In a fourth aspect, the present application provides a battery, comprising the negative electrode plate provided in the third aspect.
[0041] This application has the following beneficial effects:
[0042] The preparation method of the negative electrode material provided in the present application includes calcining silicon powder in hydrocarbon gas to obtain carbon-encapsulated silicon powder; preparing a cellulose dispersion containing nano-cellulose and phosphorus-nitrogen salts; mixing the carbon-encapsulated silicon powder with the cellulose dispersion, and obtaining a silicon-cellulose mixture after dehydration; preparing a negative electrode material dispersion containing the silicon-cellulose mixture and a lithium source; spraying, drying, grinding, and sintering the negative electrode material dispersion in sequence to obtain the negative electrode material. The negative electrode material of the present application belongs to a double anion-doped silicon negative electrode material, wherein the nano-cellulose can physically separate the carbon-encapsulated silicon powder to prevent it from restacking and aggregating during mixing and sintering, which is conducive to the lithium ion transmission between the double anion-doped silicon negative electrode materials. The carbonized nano-cellulose enhances the conductivity and structural stability of the negative electrode material, and can reduce the stress and strain caused by volume expansion. The doping of phosphorus and nitrogen in the phosphorus-nitrogen salt in the carbon skeleton further increases the active sites and conductivity of the negative electrode material, reduces the side reaction with the electrolyte, improves the cycle performance of the negative electrode material, and thus improves the electrochemical performance of the battery. The negative electrode material dispersion contains a lithium source. On the one hand, the addition of lithium increases the initial charge and discharge rate of the battery and increases the reversible lithium content; on the other hand, the introduction of MoP (molybdenum phosphide) can reduce the Li + Adsorption energy to promote Li + Rapid intercalation kinetics to suppress excessive Li + The accumulation on the surface of the material can prevent the large amount of Li + Transferred to the surface of the silicon negative electrode material, the interfacial Li + Excessive aggregation and increased interface deterioration reduce the electrochemical stability of the material. Therefore, the negative electrode material prepared by the preparation method provided in the present application can significantly improve the electrochemical performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 This is a scanning electron microscope image of the negative electrode material in Example 4 of the present application. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0046] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0047] The existing lithium batteries with silicon-based negative electrode materials have insufficient electrochemical performance due to the limitations of the negative electrode materials themselves. To this end, the embodiments of the present application provide a negative electrode material and a preparation method thereof, which improves the conductivity, structural stability and cycle performance of the negative electrode material by introducing a carbon layer, nano-cellulose, phosphorus and nitrogen double anion doping, and MoP into the silicon-based negative electrode material, thereby improving the electrochemical performance of the battery. The embodiments of the present application also provide a negative electrode sheet and a battery containing the above-mentioned negative electrode material.
[0048] The negative electrode material provided in the embodiment of the present application includes silicon powder, a carbon layer coated on the surface of the silicon powder, carbonized nanocellulose attached to the surface of the carbon layer, and molybdenum phosphide, and the carbon layer and / or the carbonized nanocellulose are doped with nitrogen, phosphorus, and lithium elements. Nanocellulose can enhance the structural stability of the negative electrode material; further, the nanocellulose in the negative electrode material is carbonized nanocellulose, which can increase the conductivity of the negative electrode material. The double anion doping of phosphorus and nitrogen in the carbon layer and / or nanocellulose further increases the active sites and conductivity of the negative electrode material, reduces the side reactions with the electrolyte, improves the cycle performance of the negative electrode material, and further improves the electrochemical performance. On the other hand, MoP is also introduced into the negative electrode material, which can reduce Li + Adsorption energy to promote Li + Rapidly embed the interface to suppress excessive Li + The accumulation on the surface of the negative electrode material can prevent the large amount of Li + Transferred to the surface of the negative electrode material, the interfacial Li + Excess aggregation and interface deterioration increase, thereby improving the electrochemical stability of the negative electrode material.
[0049] Optionally, the lithium content in the negative electrode material is 0.002-5wt%; the molybdenum content in the negative electrode material is 0.001-0.2wt%; the nitrogen content in the negative electrode material is below 0.8wt%, and the phosphorus content in the negative electrode material is below 0.8wt%; the particle size range of the negative electrode material is 0.2-15μm.
[0050] The embodiment of the present application provides a method for preparing a negative electrode material, which can be used to prepare the above-mentioned negative electrode material. Figure 1 This is a flow chart of a method for preparing a negative electrode material in one embodiment of the present application. Figure 1 As shown, the preparation method of the negative electrode material includes:
[0051] Step S100, calcining silicon powder in hydrocarbon gas to obtain carbon-coated silicon powder.
[0052] Optionally, step S100 specifically includes: sintering silicon powder at 700-950° C. for 1-5 hours in a mixed gas atmosphere of hydrocarbon gas and inert gas; then cooling to 400-700° C. and maintaining for 1-5 hours to obtain carbon-encapsulated silicon powder (Si / C).
[0053] Optionally, the inert gas may be argon or helium; the hydrocarbon gas may be a low-carbon chain gas with 1 to 8 carbon atoms. Further, the volume ratio of the hydrocarbon gas to the inert gas may be (1 to 5):(5 to 20).
[0054] Optionally, the particle size of the silicon powder is 0.6 to 15 μm.
[0055] Step S200, preparing a cellulose dispersion containing nano-cellulose and phosphorus-nitrogen salts.
[0056] Optionally, step S200 specifically includes: mixing the nano-cellulose with a dispersant solution, performing ultrasonic dispersion and stirring, and then adding a phosphorus-nitrogen salt to obtain the cellulose dispersion.
[0057] The dispersant solution includes at least one of dimethylformamide, sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium alkyl sulfonate. The dispersant solution can be an aqueous solution of at least one of dimethylformamide, sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium alkyl sulfonate, wherein the solute content is 0.005-0.2wt%. Optionally, 0.01-0.4kg of nano-cellulose is mixed per liter of the dispersant solution.
[0058] Optionally, the phosphorus-nitrogen salt is at least one of ammonium hydrogen phosphate, ammonium phosphate, magnesium ammonium phosphate, ammonium tripolyphosphate and ammonium polyphosphate.
[0059] Optionally, the nanocellulose is at least one of cellulose nanowhiskers, nanofibril cellulose, nanofibrillated cellulose, microfibrillated cellulose and nano bacterial cellulose. Further, the nanocellulose has a length of 50 to 500 nm and a diameter of 10 to 100 nm.
[0060] Step S300, mixing carbon-encapsulated silicon powder with cellulose dispersion, and dehydrating to obtain a silicon-cellulose mixture.
[0061] Optionally, step S300 specifically includes: adding 400 to 800 g of carbon-encapsulated silicon powder to each liter of cellulose dispersion, performing ultrasonic dispersion and stirring, heating, removing gas, and dehydrating at 100 to 110° C. to obtain a dry silicon-cellulose mixture (Si / C-NCE&P-N, wherein NCE is nano-cellulose).
[0062] Step S400, preparing a negative electrode material dispersion containing a silicon-cellulose mixture, a lithium source and a phosphorus-molybdenum compound.
[0063] Optionally, step S400 specifically includes: adding a lithium source and a phosphorus-molybdenum compound to an acid solution with a pH value of 3.5 to 6.5 to obtain a modified solution; adding 1.5 to 5 kg of a silicon-cellulose mixture per liter of the modified solution to obtain a negative electrode material dispersion.
[0064] Furthermore, the lithium source is at least one of lithium hydroxide, lithium oxalate, lithium chloride, lithium formate, lithium carbonate and phenyl lithium.
[0065] Furthermore, the acid solution is a nitric acid solution, a hydrochloric acid solution or a phosphoric acid solution.
[0066] Optionally, the phosphomolybdenum compound is at least one of ammonium phosphomolybdate, phosphomolybdic acid and molybdenum phosphide.
[0067] Step S500, spraying, drying, grinding and sintering the negative electrode material dispersion in sequence to obtain the negative electrode material.
[0068] Optionally, step S500 specifically includes: using a spraying machine to spray the negative electrode material dispersion at 45-95°C, and then drying and grinding; sintering the product at 400-900°C in a protective gas for 1-5 hours, and ball milling after cooling to obtain the negative electrode material (Si / C / Li&MoP-NCE&P-N).
[0069] The negative electrode sheet provided in the embodiment of the present application includes the negative electrode material provided in the above embodiment. The negative electrode sheet can be manufactured in the following manner.
[0070] (1) Dry mixing: The negative electrode material, graphite and conductive material are placed in a stirring tank of a mixer and dry mixed and stirred at a speed of 200 to 1500 r / min for 5 to 30 min to obtain a mixed dry powder.
[0071] (2) Wet mixing: Mix the dry powder and the binding material with deionized water in a container, and add water to the mixed slurry in the stirring tank until the solid content reaches 60-75% (preferably 65-70%). Then add the conductive material, the binding material and the deionized water, and stir and mix them evenly at a high speed of 1200-3000r / min for 30-200min. Add deionized water in an amount such that the solid content of the mixed slurry in the stirring tank is 40-60% (preferably 45-55%), adjust the viscosity to between 2.0 and 4Pa·s (preferably 2.5-3.5Pa·s), and the fineness is ≤0.25mm to obtain the negative electrode mixed slurry.
[0072] (3) coating the mixed slurry on at least one side of the negative electrode current collector, drying, rolling and cutting to obtain a negative electrode sheet. The negative electrode sheet is a double anion doped silicon-graphite negative electrode sheet.
[0073] Furthermore, in the mixture of negative electrode material, graphite, conductive material and binding material, the negative electrode material and graphite together account for 85-98.5wt% (graphite accounts for 30-96wt% in the mixture), the conductive material accounts for 0.2-7wt%, and the binding material accounts for 0.2-8.0wt%.
[0074] Optionally, the graphite is one or more graphites obtained by high-temperature graphitization of materials such as petroleum coke, asphalt glue, needle coke, etc. Optionally, the median particle size Dv50 of the graphite is between 6 and 26 μm.
[0075] The conductive material in (1) and (2) is at least one of conductive carbon black, acetylene black, graphite, graphene, carbon micro-nano linear conductive material, and carbon micro-nano tubular conductive material;
[0076] Optionally, the bonding material is a monomer, polymer or copolymer of acrylonitrile, vinylidene fluoride, vinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, methacryloyl, acrylic acid, lithium acrylate, acrylamide, amide, imide, acrylate, styrene-butadiene latex, sodium alginate, chitosan, ethylene glycol and guar gum.
[0077] Optionally, the negative electrode current collector is one of copper foil, porous copper foil, foam nickel / copper foil, galvanized copper foil, nickel-plated copper foil, carbon-coated copper foil, nickel foil, titanium foil, and carbon-containing porous copper foil.
[0078] Optionally, the positive electrode active material in the positive electrode plate is at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, lithium iron manganese phosphate and lithium iron phosphate.
[0079] The present application also provides a battery, comprising the negative electrode sheet of the present application. The battery is a lithium-ion battery.
[0080] The battery assembly method may include: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, and winding them to obtain a bare battery cell; ultrasonically welding the tabs; placing the bare battery cell in a battery shell, and drying to remove moisture; injecting an electrolyte into the battery shell, and then encapsulating to obtain a battery.
[0081] The following describes the beneficial effects of the negative electrode material preparation method, negative electrode sheet and battery provided in the embodiments of the present application in combination with various embodiments and comparative examples.
[0082] Example 1
[0083] 1. Preparation of negative electrode materials
[0084] (1) Pure silicon was ball-milled at a speed of 1200 r / min for 5 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 780°C for 3.5 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 7:3 at a heating rate of 10°C / min. The temperature was then reduced to 600°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0085] (2) Nanocellulose (nanofibril cellulose, length of 50-500 nm, diameter of 10-100 nm) and 0.01 wt% sodium hexametaphosphate solution are placed in a reaction kettle at a mass / volume ratio (kg / L) of 2:50, and ultrasonically dispersed and stirred at 55° C. for 30 min to obtain a cellulose dispersion. Then, 0.5 wt% of a phosphorus-nitrogen salt (specifically ammonium hydrogen phosphate) is added to the cellulose dispersion to obtain a cellulose dispersion.
[0086] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L: 400 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0087] (4) Acid is added to pure water until the pH value reaches 5.6, and the mixture is heated in a water bath at 65°C. Then, 1.2 wt% lithium chloride and 0.08 wt% phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 3 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, and the powder is sprayed, dried, and ground. The powder is then sent to a calcining furnace in a helium atmosphere and sintered at a constant temperature of 750°C for 4 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0088] 2. Make the negative electrode
[0089] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 800 r / min for 20 min to obtain a mixed dry powder.
[0090] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 40% sodium carboxymethyl cellulose + 40% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 71%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 100 minutes. Add deionized water until the solid content of the mixed slurry in the stirring tank is 49%, adjust the viscosity to 2.6Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 90wt%), conductive material and binder account for 95.5wt%, 2.3wt%, and 2.2wt% of the total mass, respectively. Coat the negative electrode mixed slurry on the front and back sides of the negative electrode collector (nickel-containing copper foil), dry, roll press, and cut to obtain a negative electrode sheet.
[0091] 3. Assemble the battery
[0092] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0093] Example 2
[0094] 1. Preparation of negative electrode materials
[0095] (1) Pure silicon was ball-milled at a speed of 1200 r / min for 5 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 780°C for 3.5 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 7:3 at a heating rate of 10°C / min. The temperature was then reduced to 600°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0096] (2) Nanocellulose (nanofibril cellulose, length of 50-500 nm, diameter of 10-100 nm) and 0.01 wt% sodium hexametaphosphate solution are placed in a reaction kettle at a mass / volume ratio (kg / L) of 2:50, and ultrasonically dispersed and stirred at 55° C. for 30 min to obtain a cellulose dispersion. Then, 0.5 wt% of a phosphorus-nitrogen salt (specifically ammonium hydrogen phosphate) is added to the cellulose dispersion to obtain a cellulose dispersion.
[0097] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L:500 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0098] (4) Acid is added to pure water until the pH value reaches 5.6, and the mixture is heated in a water bath at 65°C. Then, 1.2wt.% lithium chloride and 0.08wt.% phosphomolybdic acid are added and stirred to obtain a modified solution. 1L of the modified solution is sent to a spraying machine, and 3kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, which is sprayed, dried, and ground. The powder is then sent to a calcining furnace under a helium atmosphere and sintered at a constant temperature of 750°C for 4 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0099] 2. Make the negative electrode
[0100] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 800 r / min for 20 min to obtain a mixed dry powder.
[0101] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 40% sodium carboxymethyl cellulose + 40% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 71%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 100 minutes, add deionized water until the solid content of the mixed slurry in the stirring tank is 48%, adjust the viscosity to 2.8Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 90wt.%), conductive material and binder account for 95.5wt%, 2.3wt%, and 2.2wt% of the total mass, respectively. The negative electrode mixed slurry is coated on the front and back sides of the negative electrode collector (nickel-containing copper foil), dried, rolled, and cut to obtain a negative electrode sheet.
[0102] 3. Assemble the battery
[0103] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0104] Example 3
[0105] 1. Preparation of negative electrode materials
[0106] (1) Pure silicon was ball-milled at a speed of 1200 r / min for 5 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 780°C for 3.5 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 7:3 at a heating rate of 10°C / min. The temperature was then reduced to 600°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0107] (2) Nanocellulose (nanofibril cellulose, length of 50-500 nm, diameter of 10-100 nm) and 0.01 wt% sodium hexametaphosphate solution are placed in a reaction kettle at a mass / volume ratio (kg / L) of 2:50, and ultrasonically dispersed and stirred at 70°C for 50 min to obtain a cellulose dispersion. Then, a phosphorus-nitrogen salt (specifically ammonium hydrogen phosphate) accounting for 0.5 wt% of the mass of the cellulose dispersion is added to obtain a cellulose dispersion.
[0108] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L: 600 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0109] (4) Acid is added to pure water until the pH value reaches 5.6, and the mixture is heated in a water bath at 65°C. Then, 1.2 wt% lithium chloride and 0.08 wt% phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 3 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, and the powder is sprayed, dried, and ground. The powder is then sent to a calcining furnace in a helium atmosphere and sintered at a constant temperature of 750°C for 4 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0110] 2. Make the negative electrode
[0111] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 800 r / min for 20 min to obtain a mixed dry powder.
[0112] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 40% sodium carboxymethyl cellulose + 40% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 68%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 100 minutes, add deionized water until the solid content of the mixed slurry in the stirring tank is 50%, adjust the viscosity to 3.1Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 90wt%), conductive material and binder account for 95.5wt%, 2.3wt%, and 2.2wt% of the total mass, respectively. The negative electrode mixed slurry is coated on the front and back sides of the negative electrode collector (nickel-containing copper foil), dried, rolled, and cut to obtain a negative electrode sheet.
[0113] 3. Assemble the battery
[0114] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0115] Example 4
[0116] 1. Preparation of negative electrode materials
[0117] (1) Pure silicon was ball-milled at a speed of 1200 r / min for 5 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 780°C for 3.5 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 7:3 at a heating rate of 10°C / min. The temperature was then reduced to 600°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0118] (2) Nanocellulose (nanofibril cellulose, length of 50-500 nm, diameter of 10-100 nm) and 0.01 wt% sodium hexametaphosphate solution are placed in a reaction kettle at a mass / volume ratio (kg / L) of 2:50, and ultrasonically dispersed and stirred at 70°C for 50 min to obtain a cellulose dispersion. Then, a phosphorus-nitrogen salt (specifically ammonium hydrogen phosphate) accounting for 0.5 wt% of the mass of the cellulose dispersion is added to obtain a cellulose dispersion.
[0119] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L: 800 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0120] (4) Acid is added to pure water until the pH value reaches 5.6, and the mixture is heated in a water bath at 65°C. Then, 1.2 wt% lithium chloride and 0.08 wt% phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 3 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, and the powder is sprayed, dried, and ground. The powder is then sent to a calcining furnace in a helium atmosphere and sintered at a constant temperature of 750°C for 4 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0121] 2. Make the negative electrode
[0122] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 800 r / min for 20 min to obtain a mixed dry powder.
[0123] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 40% sodium carboxymethyl cellulose + 40% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 68%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 100 minutes. Add deionized water until the solid content of the mixed slurry in the stirring tank is 50%, adjust the viscosity to 3.3Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 90wt%), conductive material and binder account for 95.5wt%, 2.3wt%, and 2.2wt% of the total mass, respectively. Coat the negative electrode mixed slurry on the front and back sides of the negative electrode collector (nickel-containing copper foil), dry, roll, and cut to obtain a negative electrode sheet.
[0124] 3. Assemble the battery
[0125] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0126] Example 5
[0127] 1. Preparation of negative electrode materials
[0128] (1) Pure silicon was ball-milled at a speed of 1200 r / min for 5 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 700°C for 4 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 4:1 at a heating rate of 10°C / min. The temperature was then reduced to 650°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0129] (2) Nanocellulose (nanobacterial cellulose, length of 50-420 nm, diameter of 10-55 nm) and 0.02 wt% sodium hexametaphosphate solution were placed in a reaction kettle at a mass / volume ratio (kg / L) of 5:50, and ultrasonically dispersed and stirred at 60°C for 60 min to obtain a cellulose dispersion. Then, a phosphorus-nitrogen salt (specifically magnesium ammonium phosphate) accounting for 1.2 wt% of the mass of the cellulose dispersion was added to obtain a cellulose dispersion.
[0130] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L: 400 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0131] (4) Acid is added to pure water until the pH value reaches 5.6, and the solution is heated in a water bath at 65°C. Then, 2.8 wt% of lithium oxalate and 0.25 wt% of phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 5 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, which is sprayed, dried, and ground. The powder is then sent to a calcining furnace under a helium atmosphere and sintered at a constant temperature of 700°C for 6 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0132] 2. Make the negative electrode
[0133] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 1000 r / min for 15 min to obtain a mixed dry powder.
[0134] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 60% sodium carboxymethyl cellulose + 20% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 68%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 90 minutes, add deionized water until the solid content of the mixed slurry in the stirring tank is 52%, adjust the viscosity to 3.6Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 80wt%), conductive material and binder account for 95wt%, 2.2wt%, and 2.8wt% of the total mass, respectively. The negative electrode mixed slurry is coated on the front and back sides of the negative electrode collector (nickel-containing copper foil), dried, rolled, and cut to obtain a negative electrode sheet.
[0135] 3. Assemble the battery
[0136] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0137] Example 6
[0138] 1. Preparation of negative electrode materials
[0139] (1) Pure silicon was ball-milled at a speed of 1500 r / min for 4 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 700°C for 4 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 4:1 at a heating rate of 10°C / min. The temperature was then reduced to 650°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0140] (2) Nanocellulose (nanobacterial cellulose, with a length of 50 to 420 nm and a diameter of 10 to 55 nm) and 0.05 wt% sodium hexametaphosphate solution were placed in a reaction kettle at a mass / volume ratio (kg / L) of 4:50, and ultrasonically dispersed and stirred at 60°C for 60 min to obtain a cellulose dispersion. Then, a phosphorus-nitrogen salt (specifically magnesium ammonium phosphate) accounting for 1.2 wt% of the mass of the cellulose dispersion was added to obtain a cellulose dispersion.
[0141] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L:500 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0142] (4) Acid is added to pure water until the pH value reaches 5.3, and the solution is heated in a water bath at 65°C. Then, 2.8 wt% of lithium oxalate and 0.25 wt% of phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 5 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, which is sprayed, dried, and ground. The powder is then sent to a calcining furnace under a helium atmosphere and sintered at a constant temperature of 700°C for 6 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0143] 2. Make the negative electrode
[0144] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 1000 r / min for 15 min to obtain a mixed dry powder.
[0145] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 60% sodium carboxymethyl cellulose + 20% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 69%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 90 minutes, add deionized water until the solid content of the mixed slurry in the stirring tank is 48%, adjust the viscosity to 3.3Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 80wt%), conductive material and binder account for 95wt%, 2.2wt%, and 2.8wt% of the total mass, respectively. Coat the negative electrode mixed slurry on the front and back sides of the negative electrode collector (nickel-containing copper foil), dry, roll, and cut to obtain a negative electrode sheet.
[0146] 3. Assemble the battery
[0147] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0148] Example 7
[0149] 1. Preparation of negative electrode materials
[0150] (1) Pure silicon was ball-milled at a speed of 1500 r / min for 4 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 700°C for 4 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 4:1 at a heating rate of 10°C / min. The temperature was then reduced to 650°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0151] (2) Nanocellulose (nanobacterial cellulose, length of 50-420 nm, diameter of 10-55 nm) and 0.1 wt% sodium hexametaphosphate solution were placed in a reaction kettle at a mass / volume ratio (kg / L) of 1:50, and ultrasonically dispersed and stirred at 60°C for 60 min to obtain a cellulose dispersion. Then, a phosphorus-nitrogen salt (specifically magnesium ammonium phosphate) accounting for 1.2 wt% of the mass of the cellulose dispersion was added to obtain a cellulose dispersion.
[0152] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L: 600 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0153] (4) Acid is added to pure water until the pH value reaches 5.3, and the solution is heated in a water bath at 65°C. Then, 2.8 wt% of lithium oxalate and 0.25 wt% of phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 5 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, which is sprayed, dried, and ground. The powder is then sent to a calcining furnace under a helium atmosphere and sintered at a constant temperature of 700°C for 6 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0154] 2. Make the negative electrode
[0155] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 1000 r / min for 12 min to obtain a mixed dry powder.
[0156] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 60% sodium carboxymethyl cellulose + 20% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 67%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 90 minutes, add deionized water until the solid content of the mixed slurry in the stirring tank is 48%, adjust the viscosity to 2.6Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 80wt%), conductive material and binder account for 95wt%, 2.2wt%, and 2.8wt% of the total mass, respectively. Coat the negative electrode mixed slurry on the front and back sides of the negative electrode collector (nickel-containing copper foil), dry, roll, and cut to obtain a negative electrode sheet.
[0157] 3. Assemble the battery
[0158] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0159] Example 8
[0160] 1. Preparation of negative electrode materials
[0161] (1) Pure silicon was ball-milled at a speed of 1500 r / min for 4 h in an argon atmosphere to obtain silicon powder with a particle size of 0.6 to 9 μm. The ball-milled silicon powder was then placed in a calcining furnace and sintered at 700°C for 4 h in an atmosphere of argon and low-carbon chain gas acetylene with a volume ratio of 4:1 at a heating rate of 10°C / min. The temperature was then reduced to 650°C and kept constant for 4 h, and then the temperature was reduced to obtain carbon-encapsulated silicon powder.
[0162] (2) Nanocellulose (nanobacterial cellulose, with a length of 50 to 420 nm and a diameter of 10 to 55 nm) and 0.15 wt% sodium hexametaphosphate solution were placed in a reaction kettle at a mass / volume ratio (kg / L) of 1:50, and ultrasonically dispersed and stirred at 60°C for 60 min to obtain a cellulose dispersion. Then, a phosphorus-nitrogen salt (specifically magnesium ammonium phosphate) accounting for 1.2 wt% of the mass of the cellulose dispersion was added to obtain a cellulose dispersion.
[0163] (3) The cellulose dispersion and the carbon-coated silicon source are mixed in a reaction kettle (the ratio is 1 L: 800 g), ultrasonically dispersed and stirred for 40 min, heated, gas removed, and dehydrated at 105° C. to obtain a dry silicon-cellulose mixture.
[0164] (4) Acid is added to pure water until the pH value reaches 5.3, and the solution is heated in a water bath at 65°C. Then, 2.8 wt% of lithium oxalate and 0.25 wt% of phosphomolybdic acid are added and stirred to obtain a modified solution. 1 L of the modified solution is sent to a spraying machine, and 5 kg of a silicon-cellulose mixture is added. The modified solution is uniformly coated with the silicon-cellulose mixture powder, which is sprayed, dried, and ground. The powder is then sent to a calcining furnace under a helium atmosphere and sintered at a constant temperature of 700°C for 6 hours. The negative electrode material Si / C / Li&MoP-NCE&P-N is obtained by cooling and ball milling.
[0165] 2. Make the negative electrode
[0166] (1) Dry mixing: The negative electrode material, graphite (needle coke high temperature graphitized graphite, Dv50 is 13.7 μm), and conductive material (nanotube conductive material) are placed in a stirring tank of a mixer and dry mixed at a speed of 1000 r / min for 12 min to obtain a mixed dry powder.
[0167] (2) Wet mixing: Add a binder (20% styrene-butadiene latex + 60% sodium carboxymethyl cellulose + 20% lithium polyacrylate) and deionized water to a container, add water to the mixed slurry in the stirring tank until the solid content is 67%; then add a conductive material, a binder, and deionized water and stir at a high speed of 2500r / min for 90 minutes, add deionized water until the solid content of the mixed slurry in the stirring tank is 45%, adjust the viscosity to 2.3Pa·s, and the fineness is ≤0.25mm to obtain a negative electrode mixed slurry. Among them, the added negative electrode material + graphite (graphite accounts for 80wt%), conductive material and binder account for 95wt%, 2.2wt%, and 2.8wt% of the total mass, respectively. Coat the negative electrode mixed slurry on the front and back sides of the negative electrode collector (nickel-containing copper foil), dry, roll, and cut to obtain a negative electrode sheet.
[0168] 3. Assemble the battery
[0169] The positive electrode sheet (the positive electrode active material is 97.6wt% lithium nickel cobalt manganese oxide), the isolation film, and the negative electrode sheet are stacked in sequence and wound to obtain a bare battery cell; the pole ears are ultrasonically welded; the bare battery cell is placed in a battery shell, dried to remove moisture; the electrolyte is injected into the battery shell, and encapsulated to obtain a lithium-ion secondary battery.
[0170] Comparative Example 1
[0171] The difference from Example 1 is that in the process of preparing the negative electrode material, no phosphorus-nitrogen salt is added, no nitrogen and phosphorus double anion doping is performed, and the obtained negative electrode material is Si / C / Li&MoP-NCE.
[0172] Comparative Example 2
[0173] The difference from Example 1 is that in the process of preparing the negative electrode material, in step (2), no nano-cellulose is added, that is, the dispersion does not contain cellulose, and the obtained negative electrode material is Si / C / Li&MoP&P-N.
[0174] Comparative Example 3
[0175] The difference from Example 1 is that: in the process of preparing the negative electrode material, in step (4), the steps of "adding acid to pure water to a pH of 5.6, heating in a water bath at 65°C, adding 1.2wt% lithium chloride and 0.08wt% phosphomolybdic acid, stirring and mixing to obtain a modified solution; sending 1L of the modified solution to a spraying machine, adding 3kg of a silicon-cellulose mixture, and uniformly coating the silicon-cellulose mixture powder with the modified solution, spraying, drying, and grinding" are omitted, and the dry silicon-nanocellulose mixture obtained in step (3) is directly sent to a calcining furnace under a helium atmosphere and sintered at 750°C for 4 hours, cooled, and ball-milled to obtain the negative electrode material Si / C-NCE&P-N.
[0176] The above-mentioned Examples 1-8 and Comparative Examples 1-3 were tested, and the testing method was as follows.
[0177] 1. Test the resistance of the negative electrode materials of each embodiment and comparative example and the expansion of the negative electrode sheet at 100% SOC of the battery, specifically including:
[0178] The resistance of the negative electrode materials of each embodiment and comparative example is measured with a powder resistance meter to evaluate the conductivity of the negative electrode materials; the thickness of the negative electrode pole sheet after rolling is measured with a 10,000-degree spiral ruler; the batteries of the embodiments and comparative examples are disassembled to obtain the negative electrode pole sheets at 100% SOC, and the thickness of the negative electrode pole sheet of the battery at 100% SOC is measured with a 10,000-degree spiral ruler. The expansion rate of the negative electrode pole sheet = (pole sheet thickness at 100% SOC - pole sheet thickness after rolling) / pole sheet thickness after rolling * 100%, which is used to evaluate the expansion of the negative electrode pole sheet.
[0179] 2. Battery electrical performance measurement, including:
[0180] At room temperature 25 ℃, with the starting and ending voltages of 2.8V and 4.35V, formation and constant capacity are first carried out, and the charge and discharge ratio of the first cycle of the battery is recorded. Then, it is charged to 4.35V at 1C, and charged at a constant voltage of 4.35V until the current decreases to 0.05C, and discharged to 2.8V at 0.5C. Then, it is charged to 4.35V at 1C, and charged at a constant voltage of 4.35V until the current decreases to 0.05C, and discharged to 2.8V at 0.5C. The battery is charged and discharged in this cycle, and the percentage of the battery's charge and discharge at 200 cycles, 500 cycles to the first cycle capacity, and the number of cycles corresponding to the decay to a capacity percentage of 80% are recorded to evaluate the battery's electrochemical performance.
[0181] The test results are shown in the following table. Table 1 shows the resistance of the negative electrode material and the expansion of the negative electrode sheet; Table 2 shows the ratio of the first cycle of charge and discharge and the capacity retention rate of the battery. Figure 1 This is a scanning electron microscope image of the negative electrode material in Example 4 of the present application.
[0182] Table 1:
[0183]
[0184]
[0185] Table 2:
[0186]
[0187] It can be seen from Tables 1 and 2 that the negative electrode materials of Examples 1 to 8 using nanocellulose, doped with P and N dual anions, and attached with MoP, show higher conductivity, lower expansion rate and better cycle performance compared to Comparative Examples 1 to 3. Nanocellulose can physically separate carbon-encapsulated silicon powder to prevent it from restacking and agglomerating during mixing and sintering, which is beneficial to the transmission of lithium ions between negative electrode materials. The carbonized nanocellulose enhances the conductivity and structural stability of the negative electrode material. The phosphorus and nitrogen doped in the nanocellulose further increase the active sites and conductivity of the negative electrode material, reduce the side reactions with the electrolyte, improve the cycle performance of the material, and thus improve the electrochemical performance. By using a modified solution, on the one hand, the addition of lithium increases the rate of the first charge and discharge of the battery, and the reversible lithium content increases. On the other hand, the introduction of the MoP nanophase can reduce the Li content under the condition of high-content reversible lithium content. + Adsorption energy to promote Li + Rapid intercalation kinetics to suppress excessive Li + The accumulation on the surface of the material can prevent the large amount of Li + Transferred to the surface of the negative electrode material, the interfacial Li + Excess aggregation and interface deterioration increase, thus improving the electrochemical stability of the negative electrode material.
[0188] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a negative electrode material, characterized in that: The negative electrode material comprises silicon powder, a carbon layer coated on the surface of the silicon powder, carbonized nanocellulose attached to the surface of the carbon layer, and molybdenum phosphide, wherein the carbon layer and / or the carbonized nanocellulose are doped with nitrogen, phosphorus, and lithium elements, and the preparation method of the negative electrode material comprises: calcining silicon powder in a hydrocarbon gas to obtain carbon-coated silicon powder; preparing a cellulose dispersion containing nano-cellulose and phosphorus-nitrogen salt; Mixing the carbon-encapsulated silicon powder with the cellulose dispersion, and obtaining a silicon-cellulose mixture after dehydration; preparing a negative electrode material dispersion containing the silicon-cellulose mixture, a lithium source and a phosphorus-molybdenum compound; The negative electrode material dispersion is sprayed, dried, ground and sintered in sequence to obtain the negative electrode material.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size of the silicon powder is 0.6-15 μm.
3. The method for preparing the negative electrode material according to claim 1, characterized in that: The step of calcining silicon powder in hydrocarbon gas to obtain carbon-coated silicon powder comprises: Sintering the silicon powder at 700-950° C. for 1-5 hours in a mixed gas atmosphere of the hydrocarbon gas and the inert gas; The temperature is then lowered to 400-700° C. and maintained for 1-5 hours to obtain the carbon-encapsulated silicon powder.
4. The method for preparing the negative electrode material according to claim 3, characterized in that: The hydrocarbon gas is a low-carbon chain gas with 1 to 8 carbon atoms, and the volume ratio of the hydrocarbon gas to the inert gas is (1 to 5):(5 to 20).
5. The method for preparing the negative electrode material according to claim 1, characterized in that: The steps of preparing a cellulose dispersion containing nano-cellulose and phosphorus-nitrogen salts include: The nano-cellulose is mixed with a dispersant solution, subjected to ultrasonic dispersion and stirring, and then the phosphorus-nitrogen salt is added to obtain the cellulose dispersion; Wherein, the dispersant solution includes at least one of dimethylformamide, sodium pyrophosphate, sodium tripolyphosphate, sodium hexametaphosphate and sodium alkyl sulfonate.
6. The method for preparing the negative electrode material according to claim 5, characterized in that: Each liter of the dispersant solution is mixed with 0.01 to 0.4 kg of the nano-cellulose.
7. The method for preparing the negative electrode material according to claim 5, characterized in that: The phosphorus-nitrogen salt is at least one of ammonium hydrogen phosphate, ammonium phosphate, magnesium ammonium phosphate, ammonium tripolyphosphate and ammonium polyphosphate; the nano-cellulose is at least one of cellulose nano whiskers, nanofibril cellulose, nanofibrillated cellulose, microfibrillated cellulose and nano bacterial cellulose.
8. The method for preparing the negative electrode material according to claim 1, characterized in that: The length of the nanocellulose is 50-500nm, and the diameter is 10-100nm.
9. The method for preparing the negative electrode material according to claim 1, characterized in that: The step of mixing the carbon-encapsulated silicon powder with the cellulose dispersion and dehydrating to obtain a silicon-cellulose mixture comprises: 400-800 g of the carbon-encapsulated silicon powder is added to each liter of the cellulose dispersion, and ultrasonic dispersion and stirring are performed. After heating and gas extraction, dehydration is performed at 100-110° C. to obtain a dry silicon-cellulose mixture.
10. The method for preparing the negative electrode material according to claim 1, characterized in that: The step of preparing a negative electrode material dispersion containing the silicon-cellulose mixture, a lithium source and a phosphorus-molybdenum compound comprises: Adding the lithium source and the phosphorus-molybdenum compound into an acid solution with a pH value of 3.5 to 6.5 to obtain a modified solution; 1.5-5 kg of the silicon-cellulose mixture is added per liter of the modified solution to obtain the negative electrode material dispersion.
11. The method for preparing the negative electrode material according to claim 10, characterized in that: The lithium source is at least one of lithium hydroxide, lithium oxalate, lithium chloride, lithium formate, lithium carbonate and phenyl lithium; the acid solution is nitric acid solution, hydrochloric acid solution or phosphoric acid solution.
12. The method for preparing the negative electrode material according to claim 1, characterized in that: The step of spraying, drying, grinding and sintering the negative electrode material dispersion in sequence to obtain the negative electrode material comprises: Using a spraying machine to spray the negative electrode material dispersion at 45-95° C., and then drying and grinding; The product is sintered at 400-900° C. in a protective gas for 1-5 hours, and then ball-milled after cooling to obtain the negative electrode material.
13. The method for preparing the negative electrode material according to claim 1, characterized in that: The phosphomolybdenum compound is at least one of ammonium phosphomolybdate, phosphomolybdic acid and molybdenum phosphide.
14. A negative electrode material, characterized in that: The negative electrode material comprises silicon powder, a carbon layer coated on the surface of the silicon powder, carbonized nanocellulose and molybdenum phosphide attached to the surface of the carbon layer, wherein the carbon layer and / or the carbonized nanocellulose are doped with nitrogen, phosphorus and lithium elements, and the negative electrode material is prepared by the preparation method of the negative electrode material according to any one of claims 1 to 13.
15. The negative electrode material according to claim 14, characterized in that The lithium content in the negative electrode material is 0.002-5wt%; And / or, the molybdenum content in the negative electrode material is 0.001-0.2wt%; and / or, the nitrogen content in the negative electrode material is below 0.8 wt %, and the phosphorus content in the negative electrode material is below 0.8 wt %; And / or, the particle size of the negative electrode material is in the range of 0.2 to 15 μm.
16. A negative electrode plate, characterized in that: A negative electrode material obtained by the method for preparing a negative electrode material according to any one of claims 1 to 13, or a negative electrode material according to claim 14 or 15.
17. A battery, characterized in that: Including the negative electrode sheet as described in claim 16.
Citation Information
Patent Citations
Three-dimensional conductive networked silicon-carbon composite material and preparation method and application thereof
CN106848269A
Nanometer silicon@nitrogen-phosphorus double-doped carbon composite material and preparation method thereof
CN113193194A
Negative electrode material and preparation method and application thereof
CN114373909A
Preparation method of carbon-layer-containing silicon negative electrode material, negative electrode plate, manufacturing method of negative electrode plate and lithium ion battery
CN115377397A